Phylogenomics Reveals the Evolutionary History of Phytolacca (Phytolaccaceae) - Song, Yun; Jiang, Fan; Shi, Junxia; Wang, Chaonan; Xiang, Ning; Zhu, Shuifang (Frontiers in Plant Science, 2022)
Phytolacca is the largest genus of Phytolaccaceae. Owing to interspecific hybridization, infraspecific variation, and apparent weak genetic control of many qualitative characters, which have obscured boundaries between species, the classification and phylogenetic relationships of this genus are unclear. Native Phytolacca is disjunctly distributed in America, eastern Asia, and Africa, and the biogeographic history of the genus remained unresolved. In this study, we used the whole chloroplast genome and three markers (nrDNA, rbcL and matK) to reconstruct phylogenetic relationships within Phytolacca, analyze divergence times, and infer biogeographic histories. The phylogenetic results indicate that Phytolacca is monophyletic, which is inconsistent with the infrageneric classification based on morphology. According to the divergence time estimation, Phytolacca began to diversify at approximately 20.30 Ma during the early Miocene. Central America, including Mexico, Costa Rica, and Colombia, is the center of species diversity. Biogeographical analysis indicated five main dispersal events and Phytolacca originated from Central and South America. Birds may be the primary agents of dispersal because of the fleshy fruiting of Phytolacca. This study extended sampling and added more genetic characteristics to infer the evolutionary history of Phytolacca, providing new insights for resolving the classification and elucidating the dispersal events of Phytolacca.